2018
DOI: 10.3892/or.2018.6825
|View full text |Cite|
|
Sign up to set email alerts
|

PEA15 promotes liver metastasis of colorectal cancer by upregulating the ERK/MAPK signaling pathway

Abstract: Liver metastasis is one of the major causes of death in patients with colorectal cancer, and although treatment has improved recently, the long-term survival rate of patients has not improved significantly. In the present study, we used immunohistochemistry to determine that phosphoprotein enriched in astrocytes-15 kDa (PEA15) was highly expressed in colorectal cancer tissues and liver metastatic cancer tissues. It was also highly expressed in metastatic colorectal cancer patients compared to non-metastatic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…It has been confirmed that hepatitis B infection increases the risk of liver cancer [26,27]. Furthermore, the p53 signaling pathway, PI3K-Akt signaling pathway, and MAPK signaling pathway play critical roles in liver cancer [28][29][30]. Therefore, pathways enriched by differentially expressed mRNAs are closely correlated with liver cancer.…”
Section: Discussionmentioning
confidence: 93%
“…It has been confirmed that hepatitis B infection increases the risk of liver cancer [26,27]. Furthermore, the p53 signaling pathway, PI3K-Akt signaling pathway, and MAPK signaling pathway play critical roles in liver cancer [28][29][30]. Therefore, pathways enriched by differentially expressed mRNAs are closely correlated with liver cancer.…”
Section: Discussionmentioning
confidence: 93%
“…PEA15 is a member of the anti-apoptotic family and it functions through ERK1/2 binding and deatheffector domain [37]. It is reported that PEA15 promotes liver metastasis of colorectal cancer by ERK/MAPK signaling pathway [38]. Meanwhile, PEA15 can contribute to the AKT-regulated cisplatin resistance and is associated with the survival in gastric cancer [39].…”
Section: Discussionmentioning
confidence: 99%
“…Transwell assay was performed according to the previous description using a modified chamber (BD Falcon, San Jose, California, USA) [ 18 ]. Briefly, 7 × 104 cells were suspended and seeded onto the upper chambers.…”
Section: Methodsmentioning
confidence: 99%